2018
DOI: 10.1002/lary.27663
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammatory response to contrast agent aspiration and its mechanisms in the rat lung

Abstract: Objectives/Hypothesis Contrast agent (CA) aspiration is an established complication of upper gastrointestinal and videofluoroscopic swallow studies. The underlying molecular biological mechanisms of acute response to CA aspiration in the respiratory organs remain unclear. The aims of this study were to elucidate the histological and biological influences of three kinds of CAs on the lung and to clarify the differences in acute responses. Study Design Animal model. Methods Eight‐week‐old male Sprague Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
3
15
1
Order By: Relevance
“…Aspiration of saline, ICA, and NICA did not cause any pathological pulmonary changes and immunological responses in the chronic phase. The high‐osmolality of ICA has been associated with pulmonary congestion in the acute stage, and pulmonary congestion and edema after ICA aspiration are improved within a few days after aspiration . In the chronic stage, it is reported that the reactions to ICA aspiration considerably decreased by the 42nd day, and a similar result was obtained in this study.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Aspiration of saline, ICA, and NICA did not cause any pathological pulmonary changes and immunological responses in the chronic phase. The high‐osmolality of ICA has been associated with pulmonary congestion in the acute stage, and pulmonary congestion and edema after ICA aspiration are improved within a few days after aspiration . In the chronic stage, it is reported that the reactions to ICA aspiration considerably decreased by the 42nd day, and a similar result was obtained in this study.…”
Section: Discussionsupporting
confidence: 87%
“…In group 3, Ba particles stayed in alveolar cavities and induced prolonged pathological changes in the lung such as thickened bronchiolar and alveolar walls, and granulation of the alveoli even on day 30 after tracheal administration of Ba suspension. However, these Ba particles were not phagocytosed by many inflammatory cells comparing with those at the acute stage of the previous study . In contrast, saline, ICA, and NICA did not cause pathologic changes in the lung.…”
Section: Resultscontrasting
confidence: 49%
See 3 more Smart Citations